Solvent solutions: comparing extraction methods for edible oils and proteins in a changing regulatory landscape. Part 2: Hazards control☆ - Carré Patrick; dev Borah Chandra; Piofczyk Thomas; Gärtner Maike; Bothe Sarah; Hadjiali Sara (Oilseeds and fats, crops and lipids)
Safety is a critical consideration in the oil mill industry, particularly in the context of solvent extraction processes. This study focuses on the safety concerns associated with various solvents used in oil extraction, highlighting the potential risks to workers and end consumers, as well as environmental impacts. The analysis reveals that alcohols, such as ethanol and isopropanol, generally offer better safety profiles compared to hexane, despite presenting higher risks in terms of ATEX (explosive atmosphere) considerations at ambient temperature. These alcohols have higher electrical conductivity, which reduces the risk of electrostatic charge accumulation and subsequent ignition. However, methanol stands out as particularly hazardous due to its wide explosivity range and low minimum ignition energy. Ketones, including acetone and methyl ethyl ketone (MEK), and ethyl acetate also show relatively favourable safety characteristics. These solvents exhibit good electrical conductivity and lower toxicity levels, making them safer alternatives to hexane. Ethyl acetate and MEK are particularly noted for their compatibility with existing safety protocols and equipment. On the other hand, methanol, hexane, and dichloromethane (DCM) rank poorly in multi-criteria safety comparisons. Methanol, DCM and hexanes are presenting specific toxicities making these solvents less desirable from a safety perspective. 2-Methyloxolane (2-MeOx) occupies an intermediate position, with some improvements over hexane but challenges related to its low water miscibility and potential for peroxide formation. The study concludes that while no single solvent is superior across all safety criteria, alcohols and certain ketones could present promising alternatives to hexane if safety was the dominant criteria of selection. In an holistic approach, the possible improvements in safety brought by these solvent must be balanced by their impacts on other criteria like energy consumption, products quality, and economic affordability.